Comparison of four different categories of prosthetic feet during ramp ambulation in unilateral transtibial amputees. (October 2015) - Agrawal, Vibhor; Gailey, Robert S; Gaunaurd, Ignacio A; O'Toole, Christopher; Finnieston, Adam; Tolchin, Ronald
Background: Comparative effectiveness of prosthetic feet during ramp ambulation in unilateral transtibial amputees, who function at different Medicare Functional Classification Levels, has not been published. Objective: To determine differences in symmetry in external work between four categories of prosthetic feet in K-Level-2 and K-Level-3 unilateral transtibial amputees during ramp ascent and descent. Study design: Randomized repeated-measures trial. Methods: Ten subjects completed six testing sessions during which symmetry in external work was calculated using F-scan in-sole sensors. Between testing sessions 1 and 2, subjects received standardized functional prosthetic training. In Sessions 3–6, subjects tested four feet—solid ankle cushion heel, stationary attachment flexible endoskeleton, Talux (categories K1, K2, and K3, respectively), and Proprio-Foot (microprocessor ankle)—using a study socket and had a 10- to 14-day accommodation period with each foot. Results: During ramp descent, K-Level-2 subjects demonstrated higher symmetry in external work values with Talux and Proprio-Foot compared to the solid ankle cushion heel foot. K-Level-3 subjects also had higher symmetry in external work values with the Talux foot than the solid ankle cushion heel foot. Ramp ascent symmetry in external work values were not significantly different between feet. Conclusions: Prosthetic foot category appears to influence symmetry in external work more during decline walking than incline walking. K-Level-2 unilateral transtibial amputees achieve greater symmetry from K3 dynamic response prosthetic feet with J-shaped ankle and microprocessor ankles while descending ramps. Clinical relevance: The findings suggest that K-Level-2 unilateral transtibial amputees benefit from K3 dynamic response prosthetic feet with J-shaped ankle. These results support the prescription of K3 feet for K-Level-2 amputees who frequently negotiate ramps.